2016
DOI: 10.2135/cropsci2015.05.0276
|View full text |Cite
|
Sign up to set email alerts
|

Gene Action and Heterotic Groups of Early White Quality Protein Maize Inbreds under Multiple Stress Environments

Abstract: Food insecurity and malnutrition are major challenges facing rural populations in sub‐Saharan Africa. A total of 150 quality protein maize (Zea mays L.) (QPM) hybrids generated from 30 early‐maturing QPM inbreds plus six checks were evaluated under drought, low soil N, and Striga [Striga hermonthica (Delile) Benth.]‐infested environments in Nigeria for 2 yr. The objectives were to (i) examine the gene action conditioning the traits in the inbreds, (ii) classify them into heterotic groups using two methods, (ii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
74
6
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(96 citation statements)
references
References 50 publications
15
74
6
1
Order By: Relevance
“…The QPM inbred lines used in this study were developed from conversion of a variety of mid-altitude normal endosperm inbred lines and OPVs to QPM and this explained the observed large genetic variability for various traits. This result is consistent with reports of genetic variability in tropical and temperate QPM germplasm (Spaner et al 1992;Vasal et al 1993a;Pixley and Bjarnason 1993;Bhatnagar et al 2004;Musila et al 2010;BaduApraku and Lum 2010;Badu-Apraku et al 2016) and in opaque-2 types (Motto et al 1978;Wessel-Beaver et al 1985).…”
Section: Discussionsupporting
confidence: 93%
“…The QPM inbred lines used in this study were developed from conversion of a variety of mid-altitude normal endosperm inbred lines and OPVs to QPM and this explained the observed large genetic variability for various traits. This result is consistent with reports of genetic variability in tropical and temperate QPM germplasm (Spaner et al 1992;Vasal et al 1993a;Pixley and Bjarnason 1993;Bhatnagar et al 2004;Musila et al 2010;BaduApraku and Lum 2010;Badu-Apraku et al 2016) and in opaque-2 types (Motto et al 1978;Wessel-Beaver et al 1985).…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, Badu-Apraku et al (2015a) found SNP marker-based GD method as the most effective in classifying early yellow quality protein maize (QPM) inbreds into heterotic groups under multiple stress environments. In another study involving the grouping of early white QPM inbreds under similar multiple stress environments, using the SNPbased GD, SCA effects of grain yield, HSGCA, and HGCAMT, the SNP-based GD method was identified as the most efficient in classifying the QPM inbreds into heterotic groups (Badu-Apraku et al, 2015c). The implication of the results of these studies is that the efficiency of the heterotic grouping methods, varies with the type of genetic material being studied.…”
Section: Comparison Of the Efficiency Of The Heterotic Grouping Methodsmentioning
confidence: 99%
“…In some cases, the traits recorded were conditioned mainly by additive gene effects under stress conditions (drought, low soil nitrogen, heat stress, combined drought and heat stress, Striga) and non-stress environments [20,21,23,[26][27][28]49]. Evaluation of yellow QPM genotypes under combined drought and heat stresses showed that grain yield was influenced by non-additive gene effects in South Africa [27].…”
Section: Combining Ability Studies Of Qpm Genotypes Traits For Toleramentioning
confidence: 99%
“…[20] QPM hybrids Drought, low soil N, and Striga infested environments in Nigeria SCA effects were higher than GCA indicated the action of nonadditive genes. [21] Inbred lines and single cross hybrids…”
Section: Plant Materials Environment Combinability Referencementioning
confidence: 99%
See 1 more Smart Citation